Common Mental Disorders Among Informal Primary Caregivers of Adults With Mental Illness During the Coronavirus Disease 2019 Epidemic in Eastern Ethiopia: A Cross-Sectional Study - Abdeta, Tilahun; Desalegn, Defaru (Frontiers in Psychiatry, 2021)
Background: Coronaviruses (CoVs) are emerging respiratory viruses and cause illnesses ranging from the common cold to severe acute respiratory syndrome (SARS). Informal primary caregivers of individuals with mental illness were special populations suffering from both the burden of caring for mentally ill individuals and the danger of the Coronavirus disease 2019 (Covid-19) epidemic. Objective: To assess the prevalence and associated factors of common mental disorders (CMDs) among the informal primary caregivers of adults with mental illness during the Covid-19 epidemic. Methods: A hospital-based cross-sectional study design was conducted from July 1 to 30, 2020. A systematic random sampling technique was used to get samples of informal primary caregivers. Data were analyzed by bivariable and multivariable logistic regression analysis. In the final model variables having a p-value <0.05 were declared as associated with CMDs. Result: Out of a total of 218 informal primary caregivers, 215 responded to this study. The prevalence of CMDs was 40.5% (95% confidence interval (CI) = 36.66, 44.3%) among informal primary caregivers. Being female informal primary caregivers (Adjusted Odds Ratios (AOR) 1.98, 95%CI = 1.05, 3.76), being student informal primary caregivers (AOR 5.8, 95%CI: 1.2, 28.4), caring patients with psychosis (AOR 3.33, 95%CI: 1.12, 9.92) and caring patients with bipolar disorder (AOR 3.12, 95%CI: 1.35, 7.23) were significantly associated with CMDs. Conclusion: Our study cannot show the causal relationship due to its cross-sectional study design nature. However, this study showed relatively higher prevalence of CMDs among informal primary caregivers of adults with any mental illness during the Covid-19 epidemics relative to pre-Covid-19 times. Being a female caregiver, being a student caregiver, and caring for adults with psychosis and bipolar disorder were factors associated with CMDs. Attention should be given, and essential psychosocial care should be provided, to maintain the mental health of informal primary caregivers of individuals with mental illness especially during the Covid-19 pandemic.